Renormalization of the pomeron intercept in reggeon field theory on a transverse lattice - Masperi, L.; Roberto, V.; Ungkitchanukit, A. (North-Holland Publishing Company, 1978)
Fil: Masperi, L. Comisión Nacional de Energía Atómica; Argentina